2021
DOI: 10.3390/ijerph18179102
|View full text |Cite
|
Sign up to set email alerts
|

Increased Use of Porch or Backyard Nature during COVID-19 Associated with Lower Stress and Better Symptom Experience among Breast Cancer Patients

Abstract: Contact with nature has been used to promote both physical and mental health, and is increasingly used among cancer patients. However, the COVID-19 pandemic created new challenges in both access to nature in public spaces and in cancer care. The purpose of our study was to evaluate the change in active and passive use of nature, places of engaging with nature and associations of nature contact with respect to improvements to perceived stress and symptom experience among breast cancer patients during the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…No other differences were observed. Pearson, Breeze, Reuben, and Wyatt (2021) , USA Breast cancer patients (56, 63.1 ± 10.7, 98%, 7.1% Black, 3.6% Native American, a.8% Hispanic/Latino, 88% White) July 2020 Observational, cross-sectional, quantitative, online survey Investigate associations between changes in nature use and perceived stress Nature Self-reported frequency and engagement in nature-based active and passive activities prior and during COVID-19 Stress Perceived stress scale (PSS10) Decreased usage of parks/trails was significantly associated with higher stress (B = −2.30, p = 0.030) Pearson, Horton, et al (2021) , USA Low-income adults and older adults (86, 56.8 ± 14.6, 57%, 83% African-American) August–October 2019 June–July 2020 Observational, longitudinal/cross-sectional, quantitative, online survey + geospatial analysis Investigate associations between quality of nature views from home and mental health issues Nature Objectively assessed park view from home Self-reported access and use of nature Stress Anxiety Depression Perceived stress scale (PSS10) Patient-Reported Outcomes Measurement Information System (PROMIS) Higher visibility of greenspace was associated with higher anxiety (β = 3.97, p = 0.025), but not depression or stress. Use and accessibility were unrelated to all constructs.…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%
“…No other differences were observed. Pearson, Breeze, Reuben, and Wyatt (2021) , USA Breast cancer patients (56, 63.1 ± 10.7, 98%, 7.1% Black, 3.6% Native American, a.8% Hispanic/Latino, 88% White) July 2020 Observational, cross-sectional, quantitative, online survey Investigate associations between changes in nature use and perceived stress Nature Self-reported frequency and engagement in nature-based active and passive activities prior and during COVID-19 Stress Perceived stress scale (PSS10) Decreased usage of parks/trails was significantly associated with higher stress (B = −2.30, p = 0.030) Pearson, Horton, et al (2021) , USA Low-income adults and older adults (86, 56.8 ± 14.6, 57%, 83% African-American) August–October 2019 June–July 2020 Observational, longitudinal/cross-sectional, quantitative, online survey + geospatial analysis Investigate associations between quality of nature views from home and mental health issues Nature Objectively assessed park view from home Self-reported access and use of nature Stress Anxiety Depression Perceived stress scale (PSS10) Patient-Reported Outcomes Measurement Information System (PROMIS) Higher visibility of greenspace was associated with higher anxiety (β = 3.97, p = 0.025), but not depression or stress. Use and accessibility were unrelated to all constructs.…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%
“…Four studies reported perceived neighborhood greenery (Dzhambov et al, 2021;Lenaerts et al, 2021;Oswald et al, 2021;Ribeiro et al, 2021). Two studies assessed the changed use of greenspace (e.g., parks, botanical gardens, balconies) (Larson et al, 2022;Pearson et al, 2021). A cross-sectional study reported changes in nature sound during the pandemic compared to pre-pandemic time (Garrido-Cumbrera et al, 2021) as a possible nature contact indicator.…”
Section: Contact With Naturementioning
confidence: 99%
“…Thirteen studies (22%) reported an association between nature exposure and stress, including nine cross-sectional designs (Basu et al, 2021;Bourion-Bédès et al, 2021;Jato-Espino et al, 2022;Lõhmus et al, 2021;Mintz et al, 2021;Pearson et al, 2021;Ribeiro et al, 2021;Sansal et al, 2021;Sundara Keeren et al, 2021), two cohorts (Vos et al, 2022;Wortzel et al, 2021) and two ecological study design (Robinson et al, 2021;Yao et al, 2022) (Table 1). Of these, three studies used a 10-item perceived stress scale (PSS) (S. Cohen et al, 1983) & Bekker, 1992), one study reported 5-item interactive assessment of COVID-19 related stress, one study used mental stress index, and the remaining three studies reported self-reported 1-item question for measuring stress.…”
Section: Stressmentioning
confidence: 99%
See 2 more Smart Citations